Uma inquieta escritura: estudo e tradução de exclamaciones e vejamen de Teresa d’Ávila - Lima, Maria Graciele de (2018)
This research has as its core the study and translation of two works left by the Spanish author, Teresa of Ávila, entitled Exclamations and Vejamen, respectively. Firstly, it was taken into account the belonging of these literary productions, of mystical character, to a literary tradition developed by women, whose origin took place in the Middle Ages, among the walls of the monasteries, as well as in the Beguine communities. This tradition continued its course and surpassed the Siglo de Oro, period in which Teresa of Ávila produced her works. Secondly, a systemic view was adopted, according to which Literature manifests in society within a complex of elements that are moved by the action of social agents known as rewriters and professional readers, which focuses on the definition of what arrives or not in the hands of the so-called non-professional readers. The rewriters are critics, editors, commentators, translators, among other agents who create the image of a literary work and its author through opinions, publications, comments , translations and other contributing texts. From these parameters, it was verified that the researched works are related to the entire production corpus of Teresa of Ávila and this is a fundamental starting point for studying any part of the author's writing. In furthering the study of Exclamaciones and Vejamen, this research problematizes the classifications of Teresian works as Major or Minor, as has been done by rewriters who were, especially, theologians in their expressive majority. As a consequence, the said problematization extends to the literary canon, as it is formed, conserved and the need to enlarge it. The discussions also had as interest to show elements of aesthetic construction present in the texts analyzed, which leads to a dialogue between Mysticism and Literature, without any of these fields of knowledge and experience may be considered more important than the other. In the research process, the translation of the two works was also developed, from the perspective of Literary Studies, that is, emphasizing elements that influence the performance adopted in each of them. In order to sustain the discussions, in greater depth, the contributions of some / more scholars were sought, such as Le Goff (2014), Huizinga (2010), Franco Júnior (2001), Wemple (1990), Nogueira (2015), Certeau (2015), Milton (1998), Lefevere (2007), Reis (1992), Flotow (2013), Compagnon (2009), Hatzfeld (2002) and Weber (1990), among other contributions that resulted in a fruitful dialogue with a view to new looks on the writings of Teresa d'Avila and, as a consequence, to other religious women who produced Literature.